Effect of chromosome 5A on gene expression during cold hardening in wheat - Kocsy, Gábor (Acta Biologica Szegediensis, 2008)
Changes in the transcript profile during cold hardening, a treatment necessary for achieving the full level of freezing tolerance, were monitored in a genetic system of wheat (Triticum aestivum L.) chromosome 5A substitution lines differing in their freezing tolerance. The number of cold-responsive genes in a freezing-tolerant substitution line (146) was significantly higher than in a sensitive one (97), indicating a general relationship between the overall number of genes with altered expression and the degree of freezing tolerance. The expression of 175 genes was differentially affected in the freezing-tolerant and sensitive substitution lines. Three of them, coding for a Ca-binding protein (Cab), a cold-responsive protein (Tacr7) and a protein described in a mutant deficient in embryo and meristems (Dem), were characterised in more detail. The expression of Dem was induced only by low temperature, while the transcript level of Cab was also higher following NaCl treatment and that of Tacr7 after salicylic acid and H2O2 application.